2011
DOI: 10.1021/ac2014299
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Inorganic Improvised Explosive Device Signatures Using Laser Electrospray Mass Spectrometry Detection with Offline Classification

Abstract: The mass spectral detection of low vapor pressure, inorganic-based explosive signatures including ammonium nitrate, chlorate, perchlorate, sugar, and the constituents contained within black powder are reported using laser electrospray mass spectrometry. The ambient pressure mass spectrometry technique combining nonresonant, femtosecond laser vaporization with electrospray postionization revealed primary and secondary signatures for trace quantities of inorganic explosives. A mixture of complexation agents in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 55 publications
1
63
0
Order By: Relevance
“…141,142) Another related technique known as laser electrospray mass spectrometry (LEMS) uses a femtosecond laser for desorption and electrospray as post-ionization. 143) LEMS has been applied for analysis of a wide range of samples such as explosives, 144) smokeless powders, 145) pharmaceuticals, 146) and biological macromolecules. 147) Although laser desorption has been used as a means to generate gas-phase ions from condensed phase, these approaches demonstrated that ionization e ciency of desorbed species can be further improved by post-ionization with electrospray.…”
Section: Desorption Based Esimentioning
confidence: 99%
“…141,142) Another related technique known as laser electrospray mass spectrometry (LEMS) uses a femtosecond laser for desorption and electrospray as post-ionization. 143) LEMS has been applied for analysis of a wide range of samples such as explosives, 144) smokeless powders, 145) pharmaceuticals, 146) and biological macromolecules. 147) Although laser desorption has been used as a means to generate gas-phase ions from condensed phase, these approaches demonstrated that ionization e ciency of desorbed species can be further improved by post-ionization with electrospray.…”
Section: Desorption Based Esimentioning
confidence: 99%
“…LEMS employs an intense (~10 13 W/cm 2 ) femtosecond laser pulse to induce nonresonant vaporization of a sample. Since there is no matrix to absorb the laser energy, fragmentation may be expected with LEMS from the intense pulses; however, intact molecular ions are typically detected, as demonstrated for small biomolecules [1,2], proteins [4][5][6], lipids [7], explosives [8][9][10], smokeless powders [11], narcotics [12], pharmaceuticals [12], and tissues [13,14]. The internal energy distribution can be determined by measuring the fragmentation yield as a function of collision-induced dissociation energy in a series of thermometer ions via the survival yield method [15].…”
Section: Introductionmentioning
confidence: 99%
“…LEMS couples nonresonant femtosecond (fs) laser vaporization with ES ionization to perform ambient pressure mass analysis on a wide variety of samples, including pharmaceuticals [35], lipids [36], narcotics [37], dipeptides [34], explosives [38][39][40], and plant tissues [41,42] for phenotype classification [41]. Most importantly, investigations of lysozyme and cytochrome c revealed that the solution-phase conformation was preserved during transfer to ES droplets when an intense, nonresonant ultrafast laser was employed for vaporization [43].…”
mentioning
confidence: 99%